Linguistic Adaptation in Heritage Tourism: English Expressions and Workers’ Perceptions in Kampoeng Heritage Kajoetangan, Malang - Talita Lathifatur Rahman; Evynurul Laily Zen (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2026)
In the heritage tourism sector, English is regularly recontextualized into a localized form, usually used in practice rather than as a marker of formal fluency. Using Jaworski’s (2010) Tourism Discourse and Kachru’s (1990) World Englishes, this research analyzes how daily English expressions are positioned across several tourism professions and how local workers attach pragmatic, economic, and symbolic meanings to the language. This research is based on qualitative data collected through semi-structured interviews and observations with eight participants representing four main tourism professions— ticket sellers, tour guides, food vendors, and souvenir shop sellers—in Kampoeng Heritage Kajoetangan, Malang City, East Java Province, Indonesia. The findings show that English functions as a pragmatic communicative tool, a hospitality strategy, and a framework for local adaptation. Participants primarily used functional and repetitive expressions for greetings, transactions, and the development of tourism impacts, while maintaining a highly instrumental perception of the language. Ultimately, this research indicates a critical need for context-based English-language training for local tourism workers, prioritizing practical interaction routines over formal grammar proficiency.